2017
DOI: 10.1371/journal.pone.0169292
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Infiltration in Enhancing and Non-Enhancing Parts of Glioblastoma: A Correlation with Histopathology

Abstract: PurposeTo correlate histopathologic findings from biopsy specimens with their corresponding location within enhancing areas, non-enhancing areas and necrotic areas on contrast enhanced T1-weighted MRI scans (cT1).Materials and MethodsIn 37 patients with newly diagnosed glioblastoma who underwent stereotactic biopsy, we obtained a correlation of 561 1mm3 biopsy specimens with their corresponding position on the intraoperative cT1 image at 1.5 Tesla. Biopsy points were categorized as enhancing (CE), non-enhancin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
88
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(99 citation statements)
references
References 24 publications
6
88
2
Order By: Relevance
“…The high specificity of T 2 in comparison with TCD maps reveals that most abnormal T 2 regions correspond to regions of tumor infiltration. This relationship between high T 2 signal and invasion is in agreement with clinical findings, both with histological data showing high infiltration in the high T 2 signal region surrounding cT 1 enhancement and patient survival analysis showing a negative correlation with abnormal T 2 volume …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The high specificity of T 2 in comparison with TCD maps reveals that most abnormal T 2 regions correspond to regions of tumor infiltration. This relationship between high T 2 signal and invasion is in agreement with clinical findings, both with histological data showing high infiltration in the high T 2 signal region surrounding cT 1 enhancement and patient survival analysis showing a negative correlation with abnormal T 2 volume …”
Section: Discussionsupporting
confidence: 90%
“…T 2 imaging commonly reveals extensive regions of abnormality surrounding the cT 1 enhancing lesion. While these regions are associated with edema, several biopsy studies have demonstrated the presence of infiltrating tumor cells within them, with the extent of the hyperintensity region being inversely correlated with survival . Evaluating progression of T 2 to cT 1 abnormalities suggests that high T 2 signal regions could represent an earlier stage of tumor development.…”
mentioning
confidence: 99%
“…Neuronavigation with preoperative MRI images is typically used to judge extent of resection but several studies have highlighted the limitations and the subjectivity of such a practice as tumor infiltration can extend beyond MRI contrast-enhanced areas, and the enhancement itself poorly correlates to tissue histopathology. 3, 4 In our parallel work using DESI-MS, we were able to detect variable and even large amounts of residual tumor via NAA measurements at the resection margins, even when they appeared clear and non-enhanced by postoperative MRI, 23 remarking the utility of such a measurement.…”
Section: Discussionmentioning
confidence: 84%
“…Remarkably, and unfortunately, postoperative MRI provided no evidence of residual tumor in any of the cases except 1 and 2. Limitations in estimating extent of resection by MRI exist and are largely due to lack of correlation between MRI contrast enhancement and histological composition of the tissue, difficulties in calculating tumor volume, and the occurrence of nonenhancing tumors (4). Also, the volume of the resection cavity does not provide a true indication of the residual microscopic tumor burden (3).…”
Section: Assessment Of Disease State and Tcp At Discrete Points Nearmentioning
confidence: 99%